2012
DOI: 10.1007/s10803-012-1560-6
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: An Exploratory Study Comparing Diagnostic Outcomes for Autism Spectrum Disorders Under DSM-IV-TR with the Proposed DSM-5 Revision

Abstract: The proposed revision for Autism spectrum disorders (ASDs) in the Diagnostic and Statistical Manual of Mental Disorders--Fifth Edition (DSM-5) represents a shift from the Diagnostic and Statistical Manual of Mental Disorders--Fourth Edition, Text Revision (DSM-IV-TR). As the proposed DSM-5 criteria require a higher minimum number of symptoms to be present compared to DSM-IV-TR, there have been some concerns about the impact that this will have on diagnostic outcomes. Therefore, the current study aimed to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 9 publications
4
76
0
7
Order By: Relevance
“…For example, Matson et al [4] reported that 48% of toddlers with PDDs did not meet the new criterion, ASD. Several studies have also shown that a considerable percentage (8.8%~53.8%) of children with PDDs diagnoses did not meet ASD [2][3][4][5][6][7][8][9][10][11] (Table 3). Table 3: Characteristics of the previous studies *Reduction means the number (or rate) of cases who lost the ASD diagnosis in the draft or in relaxed rules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Matson et al [4] reported that 48% of toddlers with PDDs did not meet the new criterion, ASD. Several studies have also shown that a considerable percentage (8.8%~53.8%) of children with PDDs diagnoses did not meet ASD [2][3][4][5][6][7][8][9][10][11] (Table 3). Table 3: Characteristics of the previous studies *Reduction means the number (or rate) of cases who lost the ASD diagnosis in the draft or in relaxed rules.…”
Section: Discussionmentioning
confidence: 99%
“…Gibbs et al [7] and Taheri et al [8] demonstrated another relaxed rule which required 1/4 of the RRB dimension, resulting that more than 70% of PDDs met the ASD criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A publicação da DSM-5 propõe uma abordagem diagnóstica de PEA consideravelmente diferente daquela que é proposta pela DSM-IV. Alguns autores têm-se debruçado sobre a nova proposta dos critérios de classificação da PEA (BARTON et al, 2013;GIBBS et al, 2012), em particular a proposta de deixar de se considerarem as perturbações globais (ou pervasivas) do desenvolvimento sendo assumido de forma explícita o conceito de -espetro de autismo. A tríade clínica de incapacidades que define as PEA na DSM-IV é reduzida para dois critérios na DSM-5, ficando os déficits de interação social e os déficits da comunicação englobados num único critério, a designar como "déficits na comunicação social".…”
Section: Introductionunclassified